The grass is always greener - Calonita, Jen (Belles, 2013)
Amid preparations for their preppy Southern town's Founders Day celebration and their own shared sweet sixteen, sisters Isabelle Scott and Mirabelle Monroe long to break free from the tight constraints that come with being the daughters of a prominent public figure.